Analisa Pengaruh Brand Kota Lama Terhadap Bentuk Logo Kafe Tekodeko - The Marchelia (TUTURRUPA, 2018)
Tekodeko Cafe sells food and beverage products that related with coffee with the support ofthe classic atmosphere because it is adjacent to the tourist area of the Old City ofSemarang. This study aims to determine the impact of the Brand Image of an area on theformation of cafe logos located within the old city area with a case study of Tekodeko café.This research used interview and questionnaire method. The result of this research can beconcluded that Tekodeko has strong reason in forming the brand that is building aconducive place for the community of art.